1981
DOI: 10.1007/bf03160460
|View full text |Cite
|
Sign up to set email alerts
|

National survey of planted salt marshes (Vegetative stabilization and wave stress)

Abstract: There have been many recent attempts to establish salt marshes in the coastal United States. Plantings are generally made for the purpose of shore protection, dredged material stabilization, or habitat development. During 1980 a survey was made of recent and historic salt marsh planting projects. Data were collected in 104 planted marshes in 12 coastal states. The relative stability of these plantings was compared to physical indicators of wave climate severity (fetch, shore slope, offshore depth, shore config… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…Erosion is triggered based on sufficient fetch (the distance across which wind-driven waves can be formed). If the fetch is greater than 9 km, the model assumes horizontal erosion at a given user defined rate (Knutson et al 1981). As the fetch for the Sundarbans is much greater than 9 km, so the seaward limit has to be chosen far enough from the seaward margin of the Sundarbans to guarantee that the threshold fetch is reached along the entire sea coast.…”
Section: Sea Level Affects Marshes Modelmentioning
confidence: 99%
“…Erosion is triggered based on sufficient fetch (the distance across which wind-driven waves can be formed). If the fetch is greater than 9 km, the model assumes horizontal erosion at a given user defined rate (Knutson et al 1981). As the fetch for the Sundarbans is much greater than 9 km, so the seaward limit has to be chosen far enough from the seaward margin of the Sundarbans to guarantee that the threshold fetch is reached along the entire sea coast.…”
Section: Sea Level Affects Marshes Modelmentioning
confidence: 99%
“…For example, in the winter of 1928, a property owner on the eastern shore of Chesapeake Bay planted smooth cordgrass (Spartina alterniflora) along more than 1 kilometer (0.5 mile) of shoreline in an attempt to reduce erosion. This shoreline has remained stable for more than 5 0 years and is the oldest reported example of shore stabilization with salt marsh vegetation in the United States (Knutson et al 1981) as shown in Figure 6 (c) Hall and Ludwig (1975) evaluated the potential use of marsh plants for erosion control in the Great Lakes. They concluded that there were few natural areas suitable for this method of shore protection because there are few sheltered shorelines.…”
Section: -1 (2) Erosion Control Plantingsmentioning
confidence: 92%
“…A practical minimum planting width for successful erosion control is 6 meters (20 feet) (Knutson et al 1981). On the Atlantic and Gulf coasts, marsh plants will typically grow in the entire intertidal zone in microtidal areas and to mean tide where tidal ranges are broader.…”
Section: (B)mentioning
confidence: 99%
“…Another form of hydrologic restoration involves reconnection of impounded areas to normal tidal influence (Brockmeyer et al 1997, Turner and. Of course, standard guidelines for coastal wetland restoration that call for limited exposure to long fetches or other sources of wave energy, such as barge or ship traffic, cannot be ignored (Knutson et al 1981).…”
Section: The Single Most Important Factormentioning
confidence: 99%